JOTT: When Things Disappear . . . and Come Back or Relocate – And Why it Really Happens by Mary Rose Barringto - Braude, Stephen (Journal of Scientific Exploration, 2019)
This book accomplishes the nearly miraculous achievement of being both substantive and highly entertaining. According to Barrington, “JOTT,” derived from “Just One of Those Things,” stands for a kind of “spatial discontinuity”—namely, a motley class of events in which objects appear or disappear in mysterious ways. For example, some can be classified as “Walkabouts,” in which “an article disappears from the place where it was known to have been and is found in another place.” Similarly, in “Comebacks,” “a known article disappears from the place where it was known to have been and later is found back in the same place.” And in “Turn-ups,” “a known article from an uncertain location appears in a place where it is known not to have been before it was found there.” The other primary categories in Barrington’s taxonomy are Flyaway, Windfall, and Trade-in (the reader might be able to guess what these are). The central contention of this book is that JOTT phenomena merit the attention of psi researchers and theorists of the paranormal. I’ve often lamented that lab research in parapsychology is premature, because we have no decent idea what kind of organic function scientists are trying to investigate under inevitably straitjacketed laboratory conditions. Not only are we ignorant of psi's finer‑grained features, we don't even know what its natural history might be–for example, whether it has an evolutionary role or primary or overall purpose or function (although there=s no shortage of speculation on these matters). Of course, there=s no reason to think that psychic phenomena occur only for parapsychologists, much less only when those parapsychologists set out to look for them. After all, a major motivation for conducting formal studies is that we have evidence of psi occurring spontaneously in life. Moreover, there are good reasons for thinking that psi might be triggered unconsciously or subconsciously, in which case it might also occur surreptitiously. But since we=re a very long way from understanding the nature and function of everyday psi, we don't know whether psychic functioning is an ability (like musical ability) or whether it=s a brute endowment such as the capacity to see or to move one's limbs. Obviously, then, in the absence of this rudimentary knowledge, we have no idea whether (or to what extent) our experimental procedures are even appropriate to the phenomena. After all, many human capacities or endowments are situation-sensitive and can only be evaluated in real-life contexts.